New treatments in membranous glomerulopathy - from the pitfalls of rituximab to a new era of biological treatments - Ferreira,Filipa (2020)
Primary membranous nephropathy (PMN) is the main cause of nephrotic syndrome in adults. The recognition that this kidney-specific disease is the result of an autoimmune process has changed diagnostic and therapeutic approaches. The determination of anti-phospholipase A2 receptor and thrombospondin type-1 domain containing 7A, when available, are part of the diagnostic and therapeutic monitoring workup. More recently, more putative antigens have been discovered. Treatment of PMN relies on optimal supportive care but immunosuppression is indicated in patients at risk of progressive kidney injury. Immunosuppression schemes commonly used are cyclophosphamide/steroids (modified Ponticelli), calcineurin inhibitors/steroids and, after the MENTOR trial, rituximab has also been considered a first-line agent in non-severe cases. However, even in the MENTOR trial, 40% of patients did not achieve remission. Rituximab-resistant PMN cases have been published. Many mechanisms have been implicated in rituximab resistance, such as the development of anti-drug antibodies, interindividual variability in drug levels, consumption of drug by internalization of the complex rituximab-CD20, the pool of autoreactive B-cells that is in circulation available for drug action, drug wasting in urine through proteinuria and also epitope spreading. Recognition and knowledge of some of these specific mechanisms of resistance has led to the use of other biologic agents. New monoclonal antibodies targeting CD20 have been developed and can be a rescue therapy for resistance PMN cases. However, as even these new-generation agents do not target memory plasma cells, therapies targeting these cells are promising. Inhibition of factors that activate autoreactive B-cells may also become an option. Additionally, a better understanding of the complement-mediated mechanisms of injury in PMN may bring to the pipeline novel biological therapies for this disease.